Spider Mites Singly Infected With Either Wolbachia or Spiroplasma Have Reduced Thermal Tolerance - Zhu, Yu-Xi; Song, Zhang-Rong; Zhang, Yi-Yin; Hoffmann, Ary A.; Hong, Xiao-Yue (Frontiers in Microbiology, 2021)
Heritable symbionts play an essential role in many aspects of host ecology in a temperature-dependent manner. However, how temperature impacts the host and their interaction with endosymbionts remains largely unknown. Here, we investigated the impact of moderate (20°C) and high (30°C and 35°C) temperatures on symbioses between the spider mite Tetranychus truncatus and two maternally inherited endosymbionts (Wolbachia and Spiroplasma). We found that the thermal tolerance of mites (as measured by survival after heat exposure) was lower for mites that were singly infected with either Wolbachia or Spiroplasma than it was for co-infected or uninfected mites. Although a relatively high temperature (30°C) is thought to promote bacterial replication, rearing at high temperature (35°C) resulted in losses of Wolbachia and particularly Spiroplasma. Exposing the mites to 20°C reduced the density and transmission of Spiroplasma but not Wolbachia. The four spider mite strains tested differed in the numbers of heat shock genes (Hsps) induced under moderate or high temperature exposure. In thermal preference (Tp) assays, the two Wolbachia-infected spider mite strains preferred a lower temperature than strains without Wolbachia. Our results show that endosymbiont-mediated spider mite responses to temperature stress is complex, involving a combination of changing endosymbiont infection patterns, altered thermoregulatory behavior, and transcription responses.